POLA RESPIRASI DAN PEMASAKAN BUAH AVOKAD - H. SUTARNO; M.H. SIAGIAN (Research Center for Biology-Indonesian Institute of Sciences, 1986)
H. SUTARNO & M.H. SIAGIAN, 1986.respiration type and ripening of avocado fruits. Berita Biologi 3(6) : 283 - 286. Respiratiqn late and ripening of avocado fruits under storage at 25°, 28 ± 1°, 31°, and 33°C were investigated. Respiration, rate increased obviously after stored for seven days. The longest ripening period was six days i.e. from 6th to 11th days under 31°C storage.The best ripening fruit performance was obtained from storage at 31°C and 28±1°C for 7 days.